Catalyst, preparation method and application thereof, and method for preparing methanol
By using a catalyst composed of a specific proportion of metal elements, the problem of low selectivity of methanol and reduced CO2 conversion of methanol catalysts prepared by hydrogenation of carbon dioxide in the prior art is solved, and efficient and stable methanol synthesis is achieved.
Patent Information
- Application Number
- CN202211551094.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-05
AI Technical Summary
The existing catalysts for preparing methanol by hydrogenation of carbon dioxide have problems such as low selectivity of methanol and reduced CO2 conversion.
A catalyst containing the first metal oxide and the second metal oxide is used, and the molar ratio of the metal element of the first metal oxide is Cu:Zn:Al:Zr:Fe:Bi=(3-6):(2 ~4): (0~1.5): (0~1.0): (0~0.5): (0~0.5), the molar ratio of the metal element of the second metal oxide is Al:Fe:Mn=(8.5~10 ): (0.1-5): (0-5), the catalyst is prepared by co-precipitation method and impregnation method, and the reaction is carried out under conditions of 200-300°C.
The conversion rate of carbon dioxide and methanol yield are improved, the thermal stability and selectivity of the catalyst are enhanced, the generation of by-products is avoided, and the purity of methanol is improved.
Smart Images

Figure BDA0003981105850000101 
Figure BDA0003981105850000111 
Figure BDA0003981105850000112
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon dioxide conversion, and specifically to a catalyst, a preparation method and application thereof, and a method for preparing methanol. Background Art
[0002] The common method of producing methanol is to use carbon dioxide hydrogenation to produce methanol. Currently, commonly used catalysts include copper-based catalysts and indium-based catalysts, but the methanol selectivity is not high, and as these catalysts deactivate during the catalytic process, the methanol selectivity will further decrease, thereby reducing the CO2 conversion rate. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide a catalyst and its preparation method and application, and a methanol preparation method, which can solve the problems of low selectivity of current methanol synthesis catalysts for methanol and decreased conversion rate of CO2.
[0004] Some embodiments of the present application provide a catalyst comprising a first metal oxide and a second metal oxide.
[0005] Wherein, the first metal oxide contains the following metal elements and their molar ratios are: Cu: Zn: Al: Zr: Fe: Bi = (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5); (0-0.5). In each embodiment of the present application, the above metal elements can be represented by their salts, for example, the molar ratio of Cu salt: Zn salt: Al salt: Zr salt: Fe salt: Bi salt = (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5); (0-0.5). The same applies to the following.
[0006] The first metal oxide may contain the following metal elements and their molar ratio may also be Cu:Zn:Al:Zr:Fe:Bi=(3-6):(2-4):(0.01-1.5):(0.01-1.0):(0.01-0.5):(0.01-0.5).
[0007] The second metal oxide contains the following metal elements and their molar ratios are Al:Fe:Mn=(8.5-10);(0.1-5);(0-5). For example, the metal elements can be represented by their salts, and the molar ratio of Al salt:Fe salt:Mn salt=(8.5-10);(0.1-5);(0-5). The anions of the above metal salts can be nitrate (NO3 - ).
[0008] The second metal oxide contains the following metal elements and their molar ratio may be Al:Fe:Mn=(8.5-10):(0.1-5):(0.01-5).
[0009] In some embodiments, the mass ratio of the first metal oxide to the second metal oxide is 1:
[0010] (0~0.10).
[0011] In some embodiments, the mass ratio of the first metal oxide to the second metal oxide is 1:
[0012] (0.05~0.08).
[0013] In some embodiments, the pore volume of the first metal oxide is 0.3 to 0.5 cm 3 / g. The specific surface area of the first metal oxide is 95 to 125 m 2 / g. The pore volume of the second metal oxide is 0.35 to 0.45 cm 3 / g. The specific surface area of the second metal oxide is 210 to 250 m 2 / g.
[0014] In some embodiments, in the first metal oxide, the molar amount of Cu is 0.3-0.6 mol, the molar amount of Zn is 0.2-0.4 mol, the molar amount of Al is 0-0.15 mol, the molar amount of Zr is 0-0.10 mol, the molar amount of Fe is 0-0.05 mol, and the molar amount of Bi is 0-0.05 mol.
[0015] In some embodiments, in the second metal oxide, the molar amount of Al is 0.085-0.1 mol; and / or, the molar amount of Fe is 0.001-0.05 mol; and / or, the molar amount of Mn is 0-0.05 mol. The second metal oxide contains Al2O3. Al2O3 is the source of the Al element.
[0016] The embodiment of the present application provides an application of the above-mentioned catalyst as a catalyst for catalyzing the reaction of CO2 and H2 to produce methanol.
[0017] In some embodiments, the catalytic temperature of the catalyst may be 200-300°C, or 210-280°C.
[0018] The present invention provides a method for preparing a catalyst, which comprises the following steps:
[0019] A first step of preparing a first metal oxide by a coprecipitation method;
[0020] a second step of preparing a second metal oxide by an impregnation method; and
[0021] The first metal oxide and the second metal oxide are mixed in a mass ratio of 1:(0-0.10) to obtain a catalyst.
[0022] In some embodiments, the preparation method of the first step comprises the following steps:
[0023] Dissolving copper salt, zinc salt, aluminum salt, zirconium salt, iron salt and bismuth salt in water in a molar ratio of (3-6):(2-4):(0-1.5):(0-1.0):(0-0.5):(0-0.5) to prepare a first solution;
[0024] dissolving the sodium salt and the base in water to prepare a second solution;
[0025] Slowly adding the first solution and the second solution into water simultaneously to obtain a suspension;
[0026] The suspension is filtered and the pH value is adjusted to below 7, and then calcined at 550-600° C. after drying, and ground after cooling to obtain a first metal oxide of 40-60 mesh.
[0027] In some embodiments, the preparation method of the second step comprises the following steps:
[0028] Dissolving iron salt and manganese salt in water at a molar ratio of (0.1-5):(0-5) to prepare a third solution;
[0029] The third solution is slowly dropped into the 40-60 mesh activated alumina, and after the surface of the activated alumina is fully infiltrated, ultrasonic washing is performed for 2-4 hours, and then the activated alumina is dried and calcined at 550-600° C., and then ground after cooling to obtain a 40-60 mesh second metal oxide.
[0030] Some embodiments of the present application provide a method for generating methanol using CO2 and H2, the method comprising the following steps:
[0031] The catalyst in the above embodiment is added into the reactor, and the temperature in the reactor is maintained at 200-300° C. and the pressure is maintained at 1.0 MPa-5.0 MPa;
[0032] A mixed gas containing CO2 and H2 at a temperature of 150-180°C is introduced into the reactor to initiate the methanol synthesis reaction; the space velocity of the mixed gas is 960 mL·h -1 ·gcat -1 ~5400mL·h -1 ·gcat -1 ;
[0033] The reaction product is subjected to gas-liquid separation to obtain a liquid product containing methanol.
[0034] In some embodiments, the amount of catalyst added may be 1 to 10 g. In some embodiments, the mass ratio of the mixed gas to the catalyst may be 1.59 / h. Alternatively, the volume ratio of the mixed gas to the catalyst may be 9000 / h. / h represents the ratio of the mass of the mixed gas flowing per hour to the mass of the catalyst, or represents the ratio of the volume of the mixed gas flowing per hour to the volume of the catalyst.
[0035] In some embodiments, the volume ratio of CO2 to H2 is 1:(2-10).
[0036] In some embodiments, the temperature within the reactor is 230°C.
[0037] In some embodiments, the pressure in the reactor is 3.0 MPa.
[0038] The numerical ranges appearing in the embodiments of the present application can be arbitrarily combined. For example, Cu: Zn: Al: Zr: Fe: Bi = (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5): (0-0.5) does not mean that the above elements need to exist at the same time, and it can only be the ratio of the molar amounts of two or more elements such as Cu: Zn = (3-6): (2-4). The same applies to other situations.
[0039] Due to the adoption of the technical solutions of the above embodiments or any combination thereof, some embodiments of the present application achieve the following beneficial effects:
[0040] The catalyst of the present application contains copper, zinc components and Al2O3 components. When Al2O3 is used in combination with copper and zinc components, the conversion rate of carbon dioxide is improved, thereby increasing the yield of methanol. In addition, the catalyst of the present application has good stability, good thermal stability, and is not easy to deactivate. Furthermore, the catalyst of the present application does not produce ethanol and other polyols, thereby increasing the purity of the methanol produced. Therefore, the catalyst in the embodiment of the present application can be used to catalyze the reaction of CO2 and H2 to produce methanol. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present application, rather than all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0042] The "embodiment" mentioned in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be arbitrarily combined or combined with other embodiments to form new embodiments.
[0043] The terms "first", "second", "third" and "fourth" etc. (if any) in this application are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" (if any) and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or modules is not limited to the listed steps or modules, but optionally includes steps or modules that are not listed, or optionally includes other steps or modules inherent to these processes, methods, products or devices.
[0044] Some embodiments of the present application provide a catalyst comprising a first metal oxide and a second metal oxide.
[0045] The first metal oxide contains the following metal elements and their molar ratios are: Cu: Zn: Al: Zr: Fe: Bi = (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5); (0-0.5). The endpoint value of 0 indicates that the element may not exist in the first metal oxide.
[0046] The above ratio can also be Cu: Zn: Al: Zr: Fe: Bi = (3-6): (2-4): (0.01-1.5): (0.01-1.0): (0.01-0.5): (0.01-0.5). The above ratio can also be Cu: Zn: Al: Zr: Fe: Bi = (4-5.5): (2.5-3.8): (0.05-1.0): (0.1-0.5): (0.05-0.2): (0.05-0.2). The above ratio can also be Cu: Zn: Al: Zr: Fe: Bi = (5-5.34): (2.67-3.56): (0.5-0.9): (0.18-0.2): (0.09-0.12): (0.09-0.12).
[0047] Adding zirconium (Zr) to the copper-zinc-aluminum catalyst can effectively improve the dispersion of the active component Cu, prevent grain aggregation during the reaction, and enhance the catalytic activity to a certain extent. At the same time, the introduction of trace Fe elements enhances the hydrogen dissociation ability of the catalytic surface and further enhances the hydrogenation effect of the catalyst.
[0048] The second metal oxide contains the following metal elements and their molar ratios are Al:Fe:Mn=(8.5-10);(0.1-5);(0-5). The above ratios can also be Al:Fe:Mn=(8.5-10):(0.1-5):(0.01-5). The above ratios can also be Al:Fe:Mn=(9.5-9.8);(1.48-2);(0.74-2).
[0049] In some embodiments, the mass ratio of the first metal oxide to the second metal oxide is 1:
[0050] (0~0.10), can also be 1:(0.05~0.08).
[0051] In some embodiments, in the first metal oxide, the content of the following elements may be: the molar amount of Cu may be 0.3 to 0.6 mol, or 0.4 to 0.55 mol, or 0.5 to 0.534 mol. The molar amount of Zn may be 0.2 to 0.4 mol, or 0.25 to 0.38 mol, or 0.267 to 0.356 mol. The molar amount of Al may be 0 to 0.15 mol, or 0.005 to 0.1 mol, or 0.05 to 0.09 mol. The molar amount of Zr may be 0 to 0.10 mol, or 0.01 to 0.05 mol, or 0.018 to 0.02 mol. The molar amount of Fe may be 0 to 0.05 mol, or 0.005 to 0.02 mol, or 0.009 to 0.012 mol. The molar amount of Bi may be 0 to 0.05 mol, 0.005 to 0.02 mol, or 0.009 to 0.012 mol.
[0052] In some embodiments, the content of the following elements in the second metal oxide may be: The molar amount of Al may be 0.085 to 0.1 mol, or 0.095 to 0.098 mol. The molar amount of Fe may be 0-0.05 mol, or 0.0148 to 0.02 mol. The molar amount of Mn may be 0-0.05 mol, or 0.0074 to 0.02 mol. The second metal oxide contains Al2O3, which serves as a source of the Al element.
[0053] In some embodiments, the pore volume of the first metal oxide may be 0.3 to 0.5 cm 3 / g, and can also be 0.31-0.46cm 3 / g. The specific surface area of the first metal oxide may be 95 to 125 m 2 / g, can also be
[0054] 97.1~121.3m 2 / g. The pore volume of the second metal oxide may be 0.35 to 0.45 cm 3 / g, and can also be 0.39 to 0.41 cm 3 / g. The specific surface area of the second metal oxide may be 210 to 250 m 2 / g, can also be 232.5~241.5m 2 / g.
[0055] The embodiment of the present application provides an application of the above catalyst as a catalyst for catalyzing the reaction of CO2 and H2 to produce methanol. The catalyst in the embodiment of the present application can improve the hydrogen dissociation and hydrogenation capacity of a single copper-based catalyst in the carbon dioxide conversion process, and improve the phenomenon of coking and aggregation of active components, and decreased conversion rate and selectivity under long-term reaction.
[0056] In some embodiments, the catalytic temperature of the catalyst may be 200-300°C, or 210-280°C.
[0057] The present invention provides a method for preparing a catalyst, which comprises the following steps:
[0058] (1) a first step of preparing a first metal oxide by a coprecipitation method;
[0059] (2) a second step of preparing a second metal oxide by an impregnation method; and
[0060] (3) Mix the first metal oxide and the second metal oxide in a mass ratio of 1:(0-0.10) to obtain a catalyst. In step (3), the two metal oxides are physically mixed.
[0061] In some embodiments, the preparation method of the first step comprises the following steps:
[0062] (1-1), dissolving a copper salt, a zinc salt, an aluminum salt, a zirconium salt (Zr), an iron salt, and a bismuth salt in water in a molar ratio of (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5): (0-0.5) to prepare a first solution;
[0063] (1-2), dissolving the sodium salt and the alkali in water to prepare a second solution;
[0064] (1-3), slowly adding the first solution and the second solution into water simultaneously to obtain a suspension;
[0065] (1-4), the suspension is filtered and the pH value is adjusted to below 7, and then the suspension is dried and calcined at 550-600°C, and then ground after cooling to obtain a first metal oxide of 40-60 mesh.
[0066] Specifically, the preparation method of the first step comprises the following steps:
[0067] Copper salt, zinc salt, aluminum salt, zirconium salt and iron salt are weighed and dissolved in deionized water according to the above ratio to prepare solution A (i.e., the first solution), and placed in a water bath at a temperature of 70° C. The above metal salts can be nitrates, such as copper nitrate, zinc nitrate, aluminum nitrate, zirconium nitrate, and iron nitrate, and the molar ratios thereof are 0.3-0.6 mol, 0.2-0.4 mol, 0-0.15 mol, 0-0.10 mol, and 0-0.05 mol, respectively.
[0068] Weigh sodium salt and sodium alkali and dissolve them in deionized water to prepare solution B (i.e., the second solution). The sodium salt can be sodium carbonate, and the sodium alkali can be sodium hydroxide.
[0069] The first solution and the second solution are slowly added to the deionized water at the same time by using a horizontal flow pump and / or a peristaltic pump, and the pH is always kept at 8 during the process, and the water bath temperature is kept at 70°C, and finally a suspension is obtained. The suspension is filtered and washed for more than 3 times, and 800 ml of deionized water is added each time for washing until the pH is ≤ 7. The filter cake is dried in an oven for 12-24 hours, placed in a muffle furnace at 550-600°C for 4-6 hours, and pressed into tablets after natural cooling, and ground into a 40-60 mesh shaped catalyst to obtain the first metal oxide.
[0070] In some embodiments, the preparation method of the second step comprises the following steps:
[0071] (2-1) Dissolve iron salt and manganese salt in water at a molar ratio of (0.1-5):(0-5) to prepare a third solution; 0 means that manganese salt does not need to be added, and the rest are the same.
[0072] (2-2) Slowly drop the third solution into the 40-60 mesh activated alumina, and after the surface of the activated alumina is fully infiltrated, ultrasonically wash for 2-4 hours, dry and roast at 550-600°C, and grind after cooling to obtain the 40-60 mesh second metal oxide. During the roasting operation: the temperature is increased by 2-5°C per minute from room temperature to 550-600°C, and maintained at 550-600°C for 300 minutes, and then cooled naturally.
[0073] Specifically, the preparation method of the second step comprises the following steps:
[0074] Weigh iron salt and manganese salt, and dissolve them in deionized water at a molar ratio of (0.1-5):(0-5) to prepare solution D (i.e., the third solution). The above-mentioned metal salts can all be nitrates, such as iron nitrate, zinc nitrate, and manganese nitrate.
[0075] Weigh activated alumina, grind it to 40-60 mesh, and measure the saturated water absorption to be 0.5-0.8 ml / gcat. Slowly add the third solution dropwise to the activated alumina. After the surface of the alumina is fully wetted, place it in an ultrasonic washing tank for washing for 2-4 hours, dry it in an oven for 12-24 hours, place it in a muffle furnace at 550-600°C for 4-6 hours, cool it naturally, and sieve it again to obtain a 40-60 mesh catalyst to obtain the second metal oxide.
[0076] Some embodiments of the present application provide a method for generating methanol using CO2 and H2, the method comprising the following steps:
[0077] (4-1) Add the catalyst in the above embodiment into the reactor, keep the temperature in the reactor at 200-300°C and the pressure at 1.0Mpa-5.0Mpa; wherein, under the conditions of laboratory test, the amount of catalyst is 1-10g, and of course it can also be 2g, 3g, 5g, 8g, 10g, etc.
[0078] (4-2) A mixed gas containing CO2 and H2 at a temperature of 150-180°C is introduced into the reactor to initiate a methanol synthesis reaction; the space velocity of the mixed gas is 960 mL·h -1 ·gcat -1 ~5400mL·h -1 ·gcat -1 ;
[0079] (4-3) The reaction product is separated into a gas-liquid phase to obtain a liquid product containing methanol.
[0080] In some embodiments, the volume ratio of CO2 and H2 is 1:(2-10), and can also be 1:(3-9), 1:(4-8) or 1:(5-6).
[0081] In some embodiments, the amount of catalyst added may be 1 to 10 g. In some embodiments, the mass ratio of the mixed gas to the catalyst may be 1.59 / h. In some embodiments, the volume ratio of the mixed gas to the catalyst may be 9000 / h. / h represents the ratio of the mass of the mixed gas flowing per hour to the mass of the catalyst, or represents the ratio of the volume of the mixed gas flowing per hour to the volume of the catalyst.
[0082] In some embodiments, the temperature within the reactor is 230°C.
[0083] In some embodiments, the pressure in the reactor is 3.0 MPa.
[0084] In some embodiments, the space velocity of the mixed gas can be 3000 mL·h -1 ·gcat -1 .
[0085] Specifically, the operation steps of using the catalyst to catalyze the raw gas to produce methanol include the following:
[0086] 1-10 g of catalyst (containing two metal oxides) is loaded into a fixed bed reactor. The raw mixed gas (CO2+H2) is heated to 150-180°C (preferably 180°C) in a ratio of 1:(2-10) in a preheating tank and then enters the fixed bed reactor. The fixed bed operating temperature is 200-300°C (preferably 230°C), the operating pressure is 1.0Mpa-5.0Mpa (preferably 3.0Mpa), and the raw mixed gas space velocity is 960mL·h -1 ·gcat -1 ~5400mL·h -1 ·gcat -1 (Preferably 3000 mL·h -1 ·gcat -1 ). After the raw mixed gas is fully contacted with the catalyst in the fixed bed reactor, a methanol synthesis reaction occurs. The reaction product is separated into gas and liquid. The liquid product contains water, methanol and other components. Methanol can be obtained after separation.
[0087] The above embodiments can be combined arbitrarily to form new embodiments.
[0088] The metal oxide catalyst (containing one metal oxide) or composite metal oxide catalyst (containing two metal oxides) provided in the present application realizes efficient production of methanol by hydrogenation of carbon dioxide.
[0089] In some embodiments of the present application, under the condition of introducing a small amount of Fe element, the hydrogenation performance of the catalyst is improved and the thermal stability of the catalyst is significantly enhanced.
[0090] In some embodiments of the present application, the introduction of composite metal oxides further enhances the CO2 hydrogenation process and improves the methanol synthesis efficiency.
[0091] In addition, the composite metal oxide catalyst provided in the present application has higher activity and stability than the traditional copper-based oxide catalyst. The composite metal oxide catalyst exhibits higher reaction activity in the hydrogenation reaction, and the CO2 conversion rate is significantly higher than that of the single copper-zinc-aluminum catalyst.
[0092] Furthermore, the presence of the iron-based (Fe) component in the composite metal oxide catalyst provided in the present application not only enhances the hydrogenation capacity of the catalyst surface, but also increases the carbon-carbon linking capacity of the catalyst surface to a certain extent, so that a series reaction relationship is formed between the first metal oxide and the second metal oxide. In the methanol synthesis, only methanol will be produced, but no by-products such as ethanol and polyols will be produced, thereby improving the yield and purity of methanol.
[0093] Experiments have shown that the CO2 conversion rate of the composite metal oxide provided in the present application can reach 38.87%, and the methanol selectivity can reach 65.24% at the same time, so it has good industrial application prospects.
[0094] The present application discloses a preparation method and application of a catalyst for producing methanol from carbon dioxide. A composite metal oxide catalyst is prepared by coprecipitation and impregnation. The preparation method of the present application mainly achieves a high conversion rate and good thermal stability of the composite catalyst under reaction conditions of 210°C to 280°C by adjusting the proportion of active catalytic components. Adding a small amount of Fe element to a methanol synthesis catalyst containing copper, zinc, aluminum and zirconium can significantly enhance the surface hydrogenation performance of the catalyst. At the same time, introducing a trace amount of modified active alumina catalyst can also help improve the carbon dioxide conversion rate. Adding Zr element to the catalyst can effectively improve the dispersion of Cu active components, increase the specific surface area of the catalyst, and thus improve the activity and stability of the catalyst. The catalyst preparation method is simple and suitable for large-scale preparation, the catalyst has excellent stability, and has good industrial application prospects.
[0095] The present application is further described below in conjunction with specific embodiments. Those skilled in the art should understand that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0096] The reagents used in the various examples of this application are shown in Table 1:
[0097] Table 1
[0098]
[0099]
[0100] The amounts of reagents used in various examples of the present application are shown in Tables 2 to 4. Table 2 relates to the first metal oxide, and Table 3 relates to the second metal oxide.
[0101] Table 2
[0102]
[0103]
[0104] Table 3
[0105]
[0106] Table 4
[0107]
[0108]
[0109] Example 1
[0110] The preparation method of the first metal oxide in this embodiment comprises the following steps:
[0111] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.267 mol 79.42 g), and Al(NO3)3·6H2O (0.090 mol 33.76 g), and dissolve them in 500 ml of deionized water to obtain solution A.
[0112] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0113] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0114] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased by 2°C per minute from room temperature to 550°C, maintained at 550°C for 300 minutes, and then cooled naturally.
[0115] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0116] The pore volume of the first metal oxide is 0.31 cm 3 / g, BET specific surface area is 97.1m 2 / g.
[0117] Catalyst performance evaluation includes the following steps:
[0118] 2g of the first metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol and water, and the gas phase product contains carbon dioxide, nitrogen, carbon monoxide, low carbon alkanes, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0119] Example 2
[0120] The preparation method of the first metal oxide of this embodiment comprises the following steps:
[0121] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.267 mol 79.42 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), and Zr(NO3)4·5H2O (0.018 mol 7.72 g), and dissolve them in 500 ml of deionized water to obtain solution A.
[0122] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0123] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0124] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0125] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0126] The pore volume of the first metal oxide is 0.37 cm 3 / g, BET specific surface area is 100.4m 2 / g.
[0127] Catalyst performance evaluation includes the following steps:
[0128] 2g of the first metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid, and the liquid phase product contains methanol and water, and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0129] Example 3
[0130] The preparation method of the first metal oxide of this embodiment comprises the following steps:
[0131] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), and Zr(NO3)4·5H2O (0.018 mol 7.72 g), and dissolve them in 500 ml of deionized water to obtain solution A.
[0132] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0133] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0134] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0135] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0136] The pore volume of the first metal oxide is 0.44 cm 3 / g, BET specific surface area is 110.9m 2 / g.
[0137] Catalyst performance evaluation includes the following steps:
[0138] 2g of the first metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid, and the liquid phase product contains methanol and water, and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0139] Example 4
[0140] The preparation method of the first metal oxide of this embodiment comprises the following steps:
[0141] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), Zr(NO3)4·5H2O (0.018 mol 7.72 g), and Fe(NO3)3·8H2O (0.009 mol 3.63 g) and dissolve them in 500 ml of deionized water to obtain solution A.
[0142] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0143] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0144] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0145] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0146] The pore volume of the first metal oxide is 0.43 cm 3 / g, BET specific surface area is 121.3m 2 / g.
[0147] Catalyst performance evaluation includes the following steps:
[0148] 2g of the first metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid, and the liquid phase product contains methanol and water, and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0149] Example 5
[0150] The preparation method of the first metal oxide of this embodiment comprises the following steps:
[0151] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), Zr(NO3)4·5H2O (0.018 mol 7.72 g), and Fe(NO3)3·8H2O (0.012 mol 4.84 g) and dissolve them in 500 ml of deionized water to obtain solution A.
[0152] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0153] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0154] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0155] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0156] The pore volume of the first metal oxide is 0.46 cm 3 / g, BET specific surface area is 119.1m 2 / g.
[0157] Catalyst performance evaluation includes the following steps:
[0158] 2g of the first metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:126:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 250°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw material space velocity was controlled at 3000mL·h -1 ·gcat -1; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid, and the liquid phase product contains methanol and water, and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0159] Example 6
[0160] The preparation method of the first metal oxide of this embodiment comprises the following steps:
[0161] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), Zr(NO3)4·5H2O (0.018 mol 7.72 g), and Fe(NO3)3·8H2O (0.009 mol 3.63 g) and dissolve them in 500 ml of deionized water to obtain solution A.
[0162] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0163] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0164] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0165] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0166] The pore volume of the first metal oxide is 0.43 cm 3 / g, BET specific surface area is 121.3m 2 / g.
[0167] The preparation method of the second metal oxide of this embodiment comprises the following steps:
[0168] Weigh Fe(NO3)3·9H2O (0.0148 mol 5.98 g) and dissolve it in 20 ml of deionized water to obtain solution D.
[0169] Weigh 10g of activated alumina (Al2O3), grind it to 40-60 mesh, slowly add solution D dropwise into the activated alumina, and place it in an ultrasonic washing tank for 2h after the surface of the alumina is fully wetted to obtain modified activated alumina.
[0170] The modified activated alumina (Al2O3) was dried for 12 hours and calcined at 550°C for 5 hours. During the calcination operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0171] The pore volume of the second metal oxide is 0.41 cm 3 / g, BET specific surface area is 232.5m 2 / g.
[0172] The preparation method of the composite metal oxide comprises the following steps:
[0173] The composite metal oxide is a physical mixture of two metal oxides, and the mass ratio of the first metal oxide to the second metal oxide is 1:0.05.
[0174] Catalyst performance evaluation includes the following steps:
[0175] 2g of composite metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw material space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol, water, etc., and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0176] Example 7
[0177] The preparation method of the first metal oxide of this embodiment comprises the following steps:
[0178] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), Zr(NO3)4·5H2O (0.018 mol 7.72 g), and Fe(NO3)3·8H2O (0.009 mol 3.63 g) and dissolve them in 500 ml of deionized water to obtain solution A.
[0179] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0180] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0181] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0182] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0183] The pore volume of the first metal oxide is 0.43 cm 3 / g, BET specific surface area is 121.3m 2 / g.
[0184] The preparation method of the second metal oxide of this embodiment comprises the following steps:
[0185] Weigh Fe(NO3)3·9H2O (0.0148 mol 5.98 g) and Mn(NO3)2 (0.0074 mol 1.325 g) and dissolve them in 20 ml of deionized water to obtain solution D. If it is a 50% diluted Mn(NO3)2, then the amount added is 0.0074 mol or 2.65 g, because the molar ratio of Mn before and after dilution remains unchanged.
[0186] Weigh 10 g of activated alumina (0.098 mol), grind it to 40-60 mesh, slowly add solution D dropwise to the activated alumina, and place it in an ultrasonic washing tank for 2 h after the surface of the alumina is fully wetted to obtain modified activated alumina.
[0187] The modified activated alumina was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0188] The pore volume of the second metal oxide is 0.39 cm 3 / g, BET specific surface area is 241.5m 2 / g.
[0189] The preparation method of the composite metal oxide comprises the following steps:
[0190] The composite metal oxide is a physical mixture of two metal oxides, and the mass ratio of the first metal oxide to the second metal oxide is 1:0.05.
[0191] Catalyst performance evaluation includes the following steps:
[0192] 2g of composite metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:126:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw material space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol, water, etc., and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0193] Example 8
[0194] The preparation method of the first metal oxide in this embodiment comprises the following steps:
[0195] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), Zr(NO3)4·5H2O (0.018 mol 7.72 g), and Fe(NO3)3·8H2O (0.012 mol 4.84 g) and dissolve them in 500 ml of deionized water to obtain solution A.
[0196] Weigh Na2CO3 (0.34 mol 59.72 g) and NaOH (0.64 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0197] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0198] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0199] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0200] The pore volume of the first metal oxide is 0.46 cm 3 / g, BET specific surface area is 119.1m 2 / g.
[0201] The preparation method of the second metal oxide of this embodiment comprises the following steps:
[0202] Weigh Fe(NO3)3·9H2O (0.0148 mol 5.98 g) and 50% Mn(NO3)2 (0.0074 mol 2.65 g) and dissolve them in 20 ml of deionized water to obtain solution D. The amount of Mn(NO3)2 added for the 50% dilution is 0.0074 mol or 2.65 g, because the molar ratio of Mn before and after dilution remains unchanged.
[0203] Weigh 10g of activated alumina, grind it to 40-60 mesh, slowly drop solution D into the activated alumina, and place it in an ultrasonic washing tank for 2h after the surface of the alumina is fully wetted to obtain modified activated alumina.
[0204] The modified activated alumina was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0205] The pore volume of the second metal oxide is 0.41 cm 3 / g, BET specific surface area is 232.5m 2 / g.
[0206] The preparation method of the composite metal oxide comprises the following steps:
[0207] The composite metal oxide is a physical mixture of two metal oxides, and the mass ratio of the first metal oxide to the second metal oxide is 1:0.05.
[0208] Catalyst performance evaluation includes the following steps:
[0209] 2g of composite metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw material space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol, water, etc., and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0210] Example 9
[0211] The preparation method of the first metal oxide in this embodiment comprises the following steps:
[0212] Weigh Cu(NO3)2·3H2O (0.534 mol 129.02 g), Zn(NO3)2·6H2O (0.356 mol 105.90 g), Al(NO3)3·6H2O (0.090 mol 33.76 g), Zr(NO3)4·5H2O (0.018 mol 7.72 g), Fe(NO3)3·8H2O (0.012 mol 4.84 g), and Bi(NO3)3·8H2O (0.012 mol 5.82 g) and dissolve them in 500 ml of deionized water to obtain solution A.
[0213] Weigh Na2CO3 (0.56 mol 59.72 g) and NaOH (1.12 mol 45.10 g) and dissolve them in 800 ml of deionized water to obtain solution B. Use a horizontal flow pump / peristaltic pump to slowly drip solution A and solution B into 300 ml of deionized water, keep the pH at 8 and the water bath temperature at 70°C, and finally obtain suspension C.
[0214] Repeatedly filter and wash (at least 3 times), adding 800 ml of deionized water each time, until the pH is ≤ 7.
[0215] The filter cake was dried for 12 hours and roasted at 550°C for 5 hours. During the roasting operation: the temperature was increased from room temperature to 550°C at a rate of 2°C per minute, maintained at 550°C for 300 minutes, and then cooled naturally.
[0216] After calcination, the catalyst is crushed into powder and tabletted at a pressure of 50-60 MPa. Finally, the powder is ground and sieved into 40-60 mesh particles to obtain the first metal oxide catalyst.
[0217] The pore volume of the first metal oxide is 0.42 cm 3 / g, BET specific surface area is 98.6m 2 / g.
[0218] Catalyst performance evaluation includes the following steps:
[0219] 2g of the first metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol, water, etc., and the gas phase product contains nitrogen, carbon monoxide, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses a clarus 580 gas chromatograph from PerkinElmer, USA, and the gas phase product analysis uses a GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0220] Comparative Example 1
[0221] The catalyst used is a commercial copper-zinc-aluminum catalyst with a pore volume of 0.30 cm 3 / g, BET specific surface area is 76.3m 2 / g.
[0222] Catalyst performance evaluation includes the following steps:
[0223] 2g of commercial copper-zinc-aluminum catalyst was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw space velocity was controlled at 3000mL·h -1 ·gcat -1 ; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol, water, ethanol, and trace polyols, and the gas phase product contains nitrogen, carbon monoxide, low carbon alkanes, low carbon olefins, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses the clarus 580 gas chromatograph of PerkinElmer Company of the United States, and the gas phase product analysis uses the GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0224] Comparative Example 2
[0225] The first metal catalyst (metal catalyst 1) is a commercial copper-zinc-aluminum catalyst with a pore volume of 0.30 cm 3 / g, BET specific surface area is 76.3m 2 / g.
[0226] The second metal catalyst (metal catalyst 2) was unmodified activated alumina with a pore volume of 0.41 cm 3 / g, BET specific surface area is 230.0m 2 / g.
[0227] The composite metal oxide is a physical mixture of two metal oxides, and the mass ratio of the first metal catalyst to the second metal catalyst is 1:0.05.
[0228] Catalyst performance evaluation includes the following steps:
[0229] 2g of composite metal oxide was loaded into the fixed bed reactor, and the mixed raw gas (CO2:H2:N2=21:63:16) was heated to 180°C by the preheater and entered the fixed bed reactor. The catalyst reduction process used a 20% hydrogen 80% nitrogen mixed gas, the reduction time was 4h, and the fixed bed operating temperature was 280°C. The catalyst reaction process operating temperature was 230°C, the reaction operating pressure was 3.0Mpa, and the synthesis gas raw material space velocity was controlled at 3000mL·h -1 ·gcat -1; After the raw materials are fully contacted with the catalyst in the reaction tube, a methanol synthesis reaction occurs. The reaction products are separated by gas and liquid. The liquid phase product contains methanol, water, ethanol, and trace polyols, and the gas phase product contains nitrogen, carbon monoxide, low carbon alkanes, low carbon olefins, etc. The reaction products are analyzed separately after passing through the gas-liquid separator. The liquid phase product analysis uses the clarus 580 gas chromatograph of PerkinElmer Company of the United States, and the gas phase product analysis uses the GC900 gas chromatograph produced by Shanghai Tianpu Instrument. The reaction results are shown in Table 5.
[0230] Table 5
[0231]
[0232]
[0233] In Table 5, CO2Conv. represents the carbon dioxide conversion rate, and CH3OHSel. represents the methanol selectivity.
[0234] As shown in Table 5, the copper-zinc-aluminum-zirconium catalyst in the embodiment has a higher conversion rate and methanol selectivity than the traditional commercial copper-zinc-aluminum catalyst. At the same time, after adding the Fe promoter to the copper-zinc-aluminum-zirconium catalyst, the catalyst conversion rate can be further improved under the same operating conditions. In addition, after physically mixing the copper-zinc-aluminum-zirconium catalyst of this embodiment with the activated alumina catalyst loaded with Fe and Mn, it was found that the mixing of a low proportion of modified alumina catalyst can contribute to the hydrogenation step of the methanol synthesis reaction, greatly improving the CO2 conversion rate. This method can greatly improve the single-pass methanol yield, and the thermal stability and life of the catalyst are also greatly improved, and it has good industrial application prospects overall.
[0235] The above-mentioned embodiments of the present application can be combined arbitrarily to form new embodiments without any creative work.
[0236] The various embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A catalyst for catalyzing the reaction of CO2 and H2 to produce methanol, characterized in that: The catalyst comprises a first metal oxide and a second metal oxide; The first metal oxide contains the following metal elements and their molar ratio is Cu: Zn: Al: Zr: Fe: Bi = (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5): (0-0.5), wherein the molar amount of Al, Zr, Fe and Bi is not 0; The second metal oxide contains the following metal elements and their molar ratio is Al:Fe:Mn=(8.5-10):(0.1-5):(0-5), wherein the molar amount of Mn is not 0; the Al element of the second metal oxide comes from Al2O3; The mass ratio of the first metal oxide to the second metal oxide is 1:(0-0.10), wherein the mass of the second metal oxide is not 0; The preparation method of the catalyst comprises the following steps: A first step of preparing a first metal oxide by a coprecipitation method; a second step of preparing a second metal oxide by an impregnation method; and Mixing the first metal oxide and the second metal oxide in a mass ratio of 1:(0-0.10) to obtain a catalyst, wherein the mass of the second metal oxide is not 0; The preparation method of the first step comprises the following steps: Dissolving a copper salt, a zinc salt, an aluminum salt, a zirconium salt, an iron salt, and a bismuth salt in water in a molar ratio of (3-6): (2-4): (0-1.5): (0-1.0): (0-0.5): (0-0.5) to prepare a first solution, wherein the molar amount of the aluminum salt, the zirconium salt, the iron salt, and the bismuth salt is not 0; dissolving the sodium salt and the base in water to prepare a second solution; Slowly adding the first solution and the second solution into water simultaneously to obtain a suspension; The suspension is filtered and the pH value is adjusted to below 7, dried and then calcined at 550-600° C., and then ground after cooling to obtain a first metal oxide of 40-60 mesh; The preparation method of the second step comprises the following steps: Dissolving an iron salt and a manganese salt in water at a molar ratio of (0.1-5):(0-5) to prepare a third solution, wherein the molar amount of the manganese salt is not 0; The third solution is slowly dropped into the 40-60 mesh activated alumina, and after the surface of the activated alumina is fully infiltrated, ultrasonic washing is performed for 2-4 hours, and then the activated alumina is dried and calcined at 550-600° C., and then ground after cooling to obtain a 40-60 mesh second metal oxide.
2. The catalyst according to claim 1, characterized in that The mass ratio of the first metal oxide to the second metal oxide is 1:(0.05-0.08); The pore volume of the first metal oxide is 0.3-0.5 cm 3 / g; and / or The specific surface area of the first metal oxide is 95-125 m 2 / g; and / or The pore volume of the second metal oxide is 0.35-0.45 cm 3 / g; and / or The specific surface area of the second metal oxide is 210-250 m 2 / g; and / or The first metal oxide contains the following metal elements and their molar ratios are Cu: Zn: Al: Zr: Fe: Bi = (3-6): (2-4): (0.01-1.5): (0.01-1.0): (0.01-0.5): (0.01-0.5); and / or The second metal oxide contains the following metal elements and their molar ratio is Al:Fe:Mn=(8.5-10):(0.1-5):(0.01-5).
3. The catalyst according to claim 1, characterized in that In the first metal oxide, the molar amount of Cu is 0.3-0.6 mol; and / or, the molar amount of Zn is 0.2-0.4 mol; and / or, the molar amount of Al is 0-0.15 mol, and the molar amount of Al is not 0; and / or, the molar amount of Zr is 0-0.10 mol, and the molar amount of Zr is not 0; and / or, the molar amount of Fe is 0-0.05 mol, and the molar amount of Fe is not 0; and / or, the molar amount of Bi is 0-0.05 mol, and the molar amount of Bi is not 0; and / or In the second metal oxide, the molar amount of Al is 0.085-0.1 mol; and / or, the molar amount of Fe is 0-0.05 mol, and the molar amount of Fe is not 0; and / or, the molar amount of Mn is 0-0.05 mol, and the molar amount of Mn is not 0.
4. Use of the catalyst according to any one of claims 1 to 3 as a catalyst for catalyzing the reaction of CO2 and H2 to produce methanol.
5. The use according to claim 4, characterized in that: The catalytic temperature of the catalyst is 200-300°C.
6. A method for preparing a catalyst according to any one of claims 1 to 3, characterized in that: The steps include: A first step of preparing a first metal oxide by a coprecipitation method; a second step of preparing a second metal oxide by an impregnation method; and The first metal oxide and the second metal oxide are mixed in a mass ratio of 1:(0-0.10) to obtain a catalyst, wherein the mass of the second metal oxide is not zero.
7. The preparation method according to claim 6, characterized in that: The preparation method of the first step comprises the following steps: Dissolving a copper salt, a zinc salt, an aluminum salt, a zirconium salt, an iron salt, and a bismuth salt in water in a molar ratio of (3-6): (2-4): (0.01-1.5): (0.01-1.0): (0.01-0.5): (0.01-0.5) to prepare a first solution, wherein the molar amount of the aluminum salt, the zirconium salt, the iron salt, and the bismuth salt is not 0; dissolving the sodium salt and the base in water to prepare a second solution; Slowly adding the first solution and the second solution into water simultaneously to obtain a suspension; The suspension is filtered and the pH value is adjusted to below 7. After drying, the suspension is calcined at 550-600° C., and after cooling, it is ground to obtain a first metal oxide of 40-60 mesh.
8. The preparation method according to claim 6, characterized in that: The preparation method of the second step comprises the following steps: Dissolving an iron salt and a manganese salt in water at a molar ratio of (0.1-5):(0-5) to prepare a third solution, wherein the molar amount of the manganese salt is not 0; The third solution is slowly dropped into the 40-60 mesh activated alumina, and after the surface of the activated alumina is fully infiltrated, ultrasonic washing is performed for 2-4 hours, and then the activated alumina is dried and calcined at 550-600° C., and then ground after cooling to obtain a 40-60 mesh second metal oxide.
9. A method for producing methanol using CO2 and H2, characterized in that: The method comprises the following steps: Add the catalyst according to any one of claims 1 to 3 into a reactor, and keep the temperature in the reactor at 200-300° C. and the pressure at 1.0 MPa-5.0 MPa; A mixed gas containing CO2 and H2 at a temperature of 150-180°C is introduced into the reactor to initiate a methanol synthesis reaction; the space velocity of the mixed gas is 960 mL·h -1 ·gcat -1 ~5400 mL·h -1 ·gcat -1 ; The reaction product is subjected to gas-liquid separation to obtain a liquid product containing methanol.
10. The method according to claim 9, characterized in that The volume ratio of the CO2 to the H2 is 1:(2-10); and / or The volume ratio of the mixed gas to the catalyst is 9000 / h; and / or The temperature in the reactor is 230°C; and / or The pressure in the reactor is 3.0 MPa.
Citation Information
Patent Citations
Catalyst for synthesizing methanol through CO2 hydrogenation as well as preparation method and application
CN103721719A
Catalysts and methods for methanol synthesis from direct hydrogenation of syngas and / or carbon dioxide
CN109310995A